2012
DOI: 10.1098/rsif.2011.0751
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the lymphatic system: challenges and opportunities

Abstract: The lymphatic system is a vital part of the circulatory and immune systems, and plays an important role in homeostasis by controlling extracellular fluid volume and in combating infection. Nevertheless, there is a notable disparity in terms of research effort expended in relation to the treatment of lymphatic diseases in contrast to the cardiovascular system. While similarities to the cardiovascular system exist, there are considerable differences in their anatomy and physiology. This review outlines some of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
208
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(213 citation statements)
references
References 82 publications
0
208
0
5
Order By: Relevance
“…Lymphatic lumen pressures have been measured by Lee [33] to be in the range up to 440 Pa. Lymphatic capillaries normally have a radius in the range of 5 µm to 15 µm [42]. However, more recent studies show that in rare cases lymphatic capillaries can reach a large radius of 30 µm [36,52]. In this model we assume a lymphatic capillary radius of 10 µm.…”
Section: Parameter Valuesmentioning
confidence: 99%
“…Lymphatic lumen pressures have been measured by Lee [33] to be in the range up to 440 Pa. Lymphatic capillaries normally have a radius in the range of 5 µm to 15 µm [42]. However, more recent studies show that in rare cases lymphatic capillaries can reach a large radius of 30 µm [36,52]. In this model we assume a lymphatic capillary radius of 10 µm.…”
Section: Parameter Valuesmentioning
confidence: 99%
“…30 Many models focus on collecting lymphatics, often considering them to be a chain of lymphangions. 4,31,32 Fewer models consider the initial lymphatics.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,44 Here, we present results of regionally applied suicide gene therapy augmenting the chemotherapy effect in these two patients who were successfully treated. A secondary treatment pathway may involve the diffusion of the 5-FU cytotoxic metabolite through the pleura porous to the lymphatic circulation 46,47 , as it has been previously observed that different concentrations of administered drug formulations enter the lymphatic circulation through the pleura porous. 48 Gene therapy studies in advance stage lung cancer patients with MPE treated with intracostal instillation of adenovirus have presented promising results.…”
Section: Discussionmentioning
confidence: 99%